2013
DOI: 10.1515/ijdhd-2012-0131
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a participative community singing program to improve health behaviors and increase physical activity in Australian Aboriginal and Torres Strait Islander people

Abstract: Background: Aboriginal and Torres Strait Islander individuals continue to experience greater levels of chronic disease than the general Australian population. Evidence suggests that increased sedentary behaviors compared with the traditional healthy and active lifestyles of this population have contributed to this situation. This investi gation aimed to examine the health benefits of a community-based singing activity intervention on chronic disease among Aboriginal and Torres Strait Islander Australians. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(36 citation statements)
references
References 10 publications
0
36
0
Order By: Relevance
“…Of these Eley et al (2010) detected improved outcomes for Study 1 but not Study 2 or for two subsequent iterations of the program. For eight interventions described in the study, observed improvements were statistically significant (O'Dea 1984; Lee et al 1994;Rowley et al 2001;d'Espaignet et al 2003;Nagel et al 2009;Eley et al 2010;Dimer et al 2013;Sun and Buys 2013). Two studies where statistical analyses were not conducted show positive directions of effects in health and wellbeing outcomes (Nel and Pashen 2003;Preuss and Brown 2006) (Table 1).…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…Of these Eley et al (2010) detected improved outcomes for Study 1 but not Study 2 or for two subsequent iterations of the program. For eight interventions described in the study, observed improvements were statistically significant (O'Dea 1984; Lee et al 1994;Rowley et al 2001;d'Espaignet et al 2003;Nagel et al 2009;Eley et al 2010;Dimer et al 2013;Sun and Buys 2013). Two studies where statistical analyses were not conducted show positive directions of effects in health and wellbeing outcomes (Nel and Pashen 2003;Preuss and Brown 2006) (Table 1).…”
Section: Discussionmentioning
confidence: 90%
“…They include visiting Country and cultural sites (O'Dea 1984;Preuss and Brown 2006), education in traditional cultural practices (Preuss and Brown 2006), hunting, fishing and eating bush foods (O'Dea 1984; Rowley et al 2001), traditional games (Kiran and Knights 2010) yarning (an Indigenous mode of talking) and sharing cultural stories (Lee et al 1994;Dimer et al 2013), mapping and activating cultural relationships of care (d'Espaignet et al 2003;Nel and Pashen 2003;Nagel et al 2009), reinforcing Elder authority (Preuss and Brown 2006) and painting, dancing, playing instruments and singing as a community (Dimer et al 2013;Sun and Buys 2013). Programs were implemented in a range of locations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations